Unveiling the unusual: a fatal case of brucellosis with multi-organ involvement - Sami, Hiba; Ahmad, Haleema; Zafar, Lubna; Varshney, Luakik; Gururaj, K.; Khan, Parvez A.; Fatima, Nazish; Khan, Haris M. (International Journal Of Community Medicine And Public Health, 2024)
Brucellosis in humans is one of the most common zoonoses. The infection is caused by various species of Brucella bacteria. Brucella infections frequently affect several organ systems with vague clinical symptoms. Humans typically acquire brucellosis through direct contact with infected animals or consumption of contaminated animal products like unpasteurized dairy. It poses significant clinical challenges due to its varied presentation. The disease manifests with a range of nonspecific symptoms including fever, sweating, fatigue, joint and muscle pain, and loss of appetite. Brucellosis can also affect various organs such as the liver, spleen, heart, and nervous system. Diagnosis often involves blood cultures, serological tests, and polymerase chain reaction (PCR) assays to detect the bacteria or antibodies produced by the immune system. This case report presents the clinical course of patient X, a 58-year-old female who succumbed to death following an unusual presentation of brucellosis. Despite initial diagnostic challenges, the identification of Brucella melitensis in her blood marked a critical turning point. The case highlights the importance of considering Brucellosis in patients with persistent fever and multi-organ involvement, emphasizing the need for early recognition and appropriate management.